Bio-oil hydrodeoxygenation over acid activated-zeolite with different Si/Al ratio - Gea, Suharman; Irvan, Irvan; Wijaya, Karna; Nadia, Asma; Pulungan, Ahmad Nasir; Sihombing, Junifa Layla; Rahayu, Rahayu (Alpha Creation Enterprise, 2022)
Bio-oil includes significant levels of oxygenate molecules, which might induce component instability and reduce its physicochemical qualities. To counteract this, the component must undergo a hydrodeoxygenation (HDO) reaction. Due to the presence of acidic active sites, zeolites have been shown to have high hydrogenation and deoxygenation capabilities. However, natural zeolite has a large number of impurities and low acidity density. Consequently, before being employed as an HDO catalyst, pretreatments such as preparation and activation are required. In this study, the catalyst used was an active natural zeolite whose acidity level varied depending on the Si/Al ratio after dealumination with 3, 5, and 7 M hydrochloric acid, proceeded by calcination with nitrogen gas flow (designated as Z3, Z5, and Z7, respectively). The results showed that dealumination and calcination of zeolite generally caused changes in its physical characteristics and components. The Z5 catalyst showed the best catalytic performance in the HDO process of bio-oil. The higher heating value (HHV) of bio-oil increased from 12 to 18 MJ/kg, the viscosity value doubled, the degree of deoxygenation increased to 77%, and the water content reduced dramatically to about one-third of that of raw bio-oil. Moreover, control compounds, such as carboxylic acids, decreased slightly, but the amount of phenol increased to about twice the content in raw bio-oil.